DNA ligase IV-deficient cells are more resistant to ionizing radiation in the absence of Ku70: Implications for DNA double-strand break repair - Adachi, Noritaka (The National Academy of Sciences, 2001)
Vertebrate cells have evolved two major pathways for repairing DNA double-strand breaks (DSBs), homologous recombination (HR) and nonhomologous DNA end-joining (NHEJ). To investigate the role of DNA ligase IV (Lig4) in DSB repair, we knocked out the Lig4 gene (LIG4) in the DT40 chicken B-lymphocyte cell line. The LIG4(−/−) cells showed a marked sensitivity to X-rays, bleomycin, and VP-16 and were more x-ray-sensitive in G(1) than late S or G(2)/M, suggesting a critical role of Lig4 in DSB repair by NHEJ. In support of this notion, HR was not impaired in LIG4(−/−) cells. LIG4(−/−) cells were more x-ray-sensitive when compared with KU70(−/−) DT40 cells, particularly at high doses. Strikingly, however, the x-ray sensitivity of KU70(−/−)/LIG4(−/−) double-mutant cells was essentially the same as that of KU70(−/−) cells, showing that Lig4 deficiency has no effect in the absence of Ku. These results indicate that Lig4 is exclusively required for the Ku-dependent NHEJ pathway of DSB repair and that other DNA ligases (I and III) do not substitute for this function. Our data may explain the observed severe phenotype of Lig4-deficient mice as compared with Ku-deficient mice.